Carta de Antonio R. Barceló a Roberto H. Todd - Barceló, Antonio R.; Todd, Roberto H. (My University, 1931)
Recomendación de Isabel Cuevas de Brunet.
Keywords: Cuevas de Brunet, Isabel; Barceló, Antonio R., 1868-1938; Brunet, Virgilio